Transient steel quality under non-isothermal conditions in a multi-strand billet caster tundish: part II. Effect of a flow-control device. (3rd July 2017) - Chatterjee, S.; Chattopadhyay, K.
Abstract : A mathematical model was built to simultaneously analyse the effects of non-isothermal conditions and flow-control device on steel quality in a real steelmaking tundish. Liquid steel was used as the operating liquid with a step-input of 23° in a full-scale delta-shaped multi-strand billet caster tundish fitted with a standard impact pad (SIP). The changes in flow pattern and temperature fields of liquid steel in the tundish under isothermal, step-up and step-down conditions were thoroughly studied. Similar to the case of a bare tundish, buoyancy effects were seen to dominate at regions away from the ladle shroud. The presence of SIP modified the flow patterns and resulted into markedly different values of RRI as compared to bare tundish. Finally, the calculated results were qualitatively compared to results obtained from a real steelmaking tundish.